Democratization beyond the post-democratic turn: towards a research agenda on new conceptions of citizen participation. Issue 3 (2nd April 2020) - Blühdorn, Ingolfur; Butzlaff, Felix
ABSTRACT: Following extensive debates about post- democracy and post- politics, scholarly attention has shifted to conceptualizing the ongoing transformation of democracy. In this endeavour, the change in understandings, expectations and functions of political participation is a key parameter. Improving citizen participation is widely regarded as the hallmark of democratization. Yet, a variety of actors are also increasingly ambivalent about democratic institutions and the further expansion of participation. Meanwhile, new forms of participation are gaining in significance – neoliberal activation, the responsibilization of consumers, digital data mining, managed behaviour guided by choice architects – which some believe much improve representation, but which others perceive as a threat to the citizens' autonomy. This article introduces a special issue focusing on the participation-democratization nexus in well-established democracies in the economically affluent global North. Based on a critical review of popular narratives of post-democracy and post-politics we sketch the notion of the post-democratic turn – which offers a new perspective on emerging forms of participation and in this special issue serves as a conceptual lens for their analysis. We then revisit more traditional conceptualizations of democratic participation which are challenged by the post-democratic turn. The article concludes with an overview of the individual contributions to this special issue.